Adverbial clauses, functional grammar, and the change from sentence grammar to discourse-text grammar - Liong, Kwee Tjoe (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Constructions commonly called adverbial clauses in traditional grammar are seen in Functional Grammar (FG) as expressions of satellites. FG’s multi-layered model of the abstract underlying clause structure assumes each single layer consists of a certain kernel structure plus some (possibly zero) appropriate operators and satellites. Each complete layer (except the top one) is embedded as the subsequent kernel at the next layer up. At each layer, operators and satellites are said to have scope over the corresponding kernel, and, thus, over all lower operators and satellites which are contained in that kernel. This paper discusses adverbial clauses which are assumed to occur as satellites at the second layer of the FG model, sometimes called circumstantials elsewhere, but in FG predication satellites, or, alternatively, level 2 satellites. It is shown that the scope of such adverbial clauses raises a problem which can’t be solved within the currently accepted model of FG and thus risks remaining a refractory case for the theoretical framework. While I don’t strive for very radical changes, and take as much as possible for granted, I prefer a different view found elsewhere which offers an elegant solution for the problem indicated here. The view in question is rejected by Dik (1997), however, and I explain why that is a regrettable mistake.